An electric vehicle dispatch module for demand-side energy participation. (1st September 2016) - Zhou, Bowen; Yao, Feng; Littler, Tim; Zhang, Huaguang
Highlights: Real-time measurement and assessment to calculate EV initial state-of-charge (SOC). Flexible EV charging allocation using measured available time duration (ATD). Owner participation using mobile phone apps and a new EV dispatch module. Online algorithm for real-time calculation of maximum and minimum adjustable limits. Business-trading models with data security, trending and commercial impacts of EV. Abstract: The penetration of the electric vehicle (EV) has increased rapidly in recent years mainly as a consequence of advances in transport technology and power electronics and in response to global pressure to reduce carbon emissions and limit fossil fuel consumption. It is widely acknowledged that inappropriate provision and dispatch of EV charging can lead to negative impacts on power system infrastructure. This paper considers EV requirements and proposes a module which uses owner participation, through mobile phone apps and on-board diagnostics II (OBD-II), for scheduled vehicle charging. A multi-EV reference and single-EV real-time response (MRS2R) online algorithm is proposed to calculate the maximum and minimum adjustable limits of necessary capacity, which forms part of decision-making support in power system dispatch. The proposed EV dispatch module is evaluated in a case study and the influence of the mobile app, EV dispatch trending and commercial impact is explored.